2019
DOI: 10.1073/pnas.1913095116
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite-mediated TOR signaling regulates the circadian clock in Arabidopsis

Abstract: Circadian clocks usually run with a period close to 24 h, but are also plastic and can be entrained by external environmental conditions and internal physiological cues. Two key nutrient metabolites, glucose and vitamin B3 (nicotinamide), can influence the circadian period in both mammals and plants; however, the underlying molecular mechanism is still largely unclear. We reveal that the target of rapamycin (TOR) kinase, a conserved central growth regulator, is essential for glucose- and nicotinamide-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 16 publications
0
45
0
Order By: Relevance
“…Sugars fluctuate as a consequence of carbon homeostasis and photosynthesis (Webb et al, 2019), whereas nicotinamide is a breakdown product of NAD acting as a substrate for post‐translational modifications including poly(ADP‐ribosyl)ation and protein deacetylation, and for the production of the Ca 2+ agonist cyclic ADP‐ribose (cADPR; Hunt, Lerner, & Ziegler, 2004). Nicotinamide lengthens circadian period in all organisms tested with proposed modes of action being through inhibition of poly(ADP‐ribose) polymerases (PARPs), sirtuins (SRTs), ADPR cyclases, the reduction of H3K4me3 accumulation, target of Rapamycin (TOR) and the action of BIG, a protein of unknown function (Asher et al, 2008; Asher et al, 2010; Dodd et al, 2007; Hearn et al, 2018; Malapeira, Crhak Khaitova, & Mas, 2012; Mombaerts et al, 2019; Nakahata et al, 2008; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sugars fluctuate as a consequence of carbon homeostasis and photosynthesis (Webb et al, 2019), whereas nicotinamide is a breakdown product of NAD acting as a substrate for post‐translational modifications including poly(ADP‐ribosyl)ation and protein deacetylation, and for the production of the Ca 2+ agonist cyclic ADP‐ribose (cADPR; Hunt, Lerner, & Ziegler, 2004). Nicotinamide lengthens circadian period in all organisms tested with proposed modes of action being through inhibition of poly(ADP‐ribose) polymerases (PARPs), sirtuins (SRTs), ADPR cyclases, the reduction of H3K4me3 accumulation, target of Rapamycin (TOR) and the action of BIG, a protein of unknown function (Asher et al, 2008; Asher et al, 2010; Dodd et al, 2007; Hearn et al, 2018; Malapeira, Crhak Khaitova, & Mas, 2012; Mombaerts et al, 2019; Nakahata et al, 2008; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, another report also suggested that TOR signaling mediates metabolite-regulated circadian clock in Arabidopsis. 18 Taken together, these findings unequivocally uncovered that TOR can feedback-regulate circadian clock in Arabidopsis.…”
Section: Resultsmentioning
confidence: 75%
“…This glucose activation of the TOR pathway is prevented by 2-deoxy-glucose and by inhibitors of the electron transport chain, indicating that glucose needs to pass through glycolysis and the electron transport chain to give TOR activation, as reported in Figure 3 [123]. In addition, it was recently reported that nicotinamide (vitamin B3) affects ATP level and inhibits the glucose-TOR signaling, regulating the circadian clock, meristem activation and root growth [124]. Although the precise molecular mechanism of glucose activation is still unknown, this last study suggests a link between the energetic status of the cell and TOR activity.…”
Section: Protein-metabolite Interactions Controlling Tor Activity In mentioning
confidence: 76%